Cilostazol: an antiplatelet agent for the neurointerventionist?. (19th December 2014) - Bhogal, P; Brouwer, P A; Makalanda, H L D
Abstract : Antiplatelet agents are essential for the successful management of patients undergoing a variety of neurointerventional procedures. The most commonly used anti-platelet agents are aspirin, clopidogrel and prasugrel. However, there exist an alternative class of anti-platelet agent that may prove useful for neurointerventionists. In particular a drug called cilostazol may have numerous added advantages above and beyond its antiplatelet effect that may be valuable for our patients. In this short review we aim to highlight some of these potential advantages.